Skills For Organizing An Entertainment Hour In A Pre-School Educational Organizations - Mahfuza Makhamadjonovna Khalilova (Euro Asian Journal Publishing, 2024)
The article talked about the skills of organizing an entertaining hour in a preschool educational organization.
Keywords: preschool education; entertainment; organization; skill